At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

15 ( y - 4 ) - 2 (y - 9 ) + 5 (y + 6) = 0

Sagot :

Answer:

y = 2/3

Step-by-step explanation:

Assuming you are looking for "y":

15 * ( y - 4 ) - 2 * (y - 9 ) + 5 * (y + 6) = 0

15y - 60 - 2y + 18 + 5y + 30 = 0

15y - 2y + 5y -60 + 18 + 30 = 0

18y = 60 - 18 - 30

18y = 12

y = 12/18

y = 2/3